2013
DOI: 10.22199/s07187475.2013.0003.00003
|View full text |Cite
|
Sign up to set email alerts
|

Estigma hacia problemas de salud mental entre profesionales de la salud en adiestramiento en Puerto Rico.

Abstract: RESUMEN El estigma hacia personas viven con problemas de salud mental ha sido identificado como una barrera en la búsqueda y adherencia a tratamiento. Según la literatura, los/as profesionales de la salud manifiestan actitudes estigmatizantes hacia esta población. Los estudios en Puerto Rico que documenten esta problemática son escasos. El objetivo de este estudio fue: (1) explorar los niveles del estigma que un grupo de Profesionales de la Salud en Adiestramiento (PSA) tiene o manifiesta hacia quienes present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
9
0
4
Order By: Relevance
“…To assess mental health stigma, a validated Spanish translation of the anonymous Mental Health Stigma Scale (MHSS) Appendix A was used, composed of 12 Likert-type questions, which students scored on a Likert scale, from 1 (strongly disagree) to 5 (strongly agree) [40]. The MHSS tool was validated, obtaining Cronbach’s alpha values between 0.67 and 0.74, with a positive correlation with another mental health and stigma scale ( r = 0.58, p < 0.01) [41].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess mental health stigma, a validated Spanish translation of the anonymous Mental Health Stigma Scale (MHSS) Appendix A was used, composed of 12 Likert-type questions, which students scored on a Likert scale, from 1 (strongly disagree) to 5 (strongly agree) [40]. The MHSS tool was validated, obtaining Cronbach’s alpha values between 0.67 and 0.74, with a positive correlation with another mental health and stigma scale ( r = 0.58, p < 0.01) [41].…”
Section: Methodsmentioning
confidence: 99%
“…The following criteria were used to calculate the sample size: Prevalence of high stigma: 15% [40], confidence level of 95%, precision (absolute error) of 3% and a population of 425 enrolled students. Based on these criteria, a minimum of 239 students was needed.…”
Section: Methodsmentioning
confidence: 99%
“…If PWSMI's main avenue for entering the pipeline of care becomes a breeding ground for stigmatizing attitudes and behaviors, the quality of the healthcare services they receive can become negatively affected or in some instances completely ignored. Alarmingly, recent research in the Puerto Rican context has also found stigmatizing attitudes towards PWSMI, including drug abuse and suicide among healthcare professionals in training, particularly among physicians in training [62,67,70]. However, in order to develop culturally sensitive stigma reduction interventions, there is still a need to understand how stigma attitudes towards PWSMI are manifested from the perspective of healthcare professionals who are currently in the field within the Puerto Rican context.…”
Section: Mental Illness Stigma and Healthcare Professionalsmentioning
confidence: 99%
“…Providers in the study were not in charge of patient's routine mental healthcare, but rather were focused on addressing physical healthcare. The selection of physicians and nurses was informed by recent literature suggesting high levels of stigma among these two specific professions [70,73]. All participants were practicing their profession in Puerto Rico and providing services in inpatient and outpatient medical institutions located in the metropolitan areas of the Island.…”
Section: Participantsmentioning
confidence: 99%
“…El mismo está institucionalizado y legitimado mediante políticas públicas (Varas-Díaz, Malavé-Rivera, & Cintrón Bou, 2008) y afecta especialmente a sectores que han sido identificados como "no gratos" socialmente como son las personas de las comunidades LGBTT, con VIH, con uso problemático de sustancias, inmigrantes, trabajadoras sexuales, entre otros. En Puerto Rico existen estudios que documentan altos niveles de estigma en profesionales de la salud (Polanco-Fronteras et al 2013;Varas-Díaz, Malavé-Rivera, & Cintrón-Bou, 2008;Varas-Díaz, Santiago-Negrón, Neilands, Cintrón-Bou, & Malavé-Rivera, 2010). Lo anterior puede apuntar a la falta de adiestramiento e intervenciones dirigidas al manejo de estigma entre profesionales de la salud.…”
Section: Discussionunclassified